2013
DOI: 10.1002/hed.23506
|View full text |Cite
|
Sign up to set email alerts
|

TPF induction chemotherapy and concomitant irradiation with cisplatin and cetuximab in unresectable squamous cell carcinoma of the head and neck

Abstract: The tested regimen was effective; however, cetuximab and low-dose cisplatin after induction TPF increased the treatment toxicity. A grade ≥ 2 skin rash correlated with improved efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…By contrast, the TPF regimen affects the administration of definitive locoregional treatment in the majority of patients with locally advanced HNSCC . The TREMPLIN trial showed that only 45% of patients receiving 3 cycles of induction TPF chemotherapy completed concomitant CRT .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the TPF regimen affects the administration of definitive locoregional treatment in the majority of patients with locally advanced HNSCC . The TREMPLIN trial showed that only 45% of patients receiving 3 cycles of induction TPF chemotherapy completed concomitant CRT .…”
Section: Discussionmentioning
confidence: 99%
“…36 By contrast, the TPF regimen affects the administration of definitive locoregional treatment in the majority of patients with locally advanced HNSCC. 22,37 The TREM-PLIN trial showed that only 45% of patients receiving 3 cycles of induction TPF chemotherapy completed concomitant CRT. 15 We strongly believe that the better tolerance profile reported in our study is due to omission of the 5-FU agent during induction chemotherapy, which needs to be better evaluated in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The TPF induction chemotherapy regimen of docetaxel, cisplatin, and fluorouracil is commonly used in advanced head and neck cancer [ 9 ]. Kong et al reported that TPF-based induction chemotherapy significantly improved clinical outcome in patients with stage III or IVA/B NPC [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to improve treatment outcome, combining chemotherapy with surgery and radiotherapy has been explored. Currently, induction chemotherapy is one of the standard treatment modalities for patients with locally advanced HNSCC to improve survival and for organ preservation …”
Section: Introductionmentioning
confidence: 99%
“…Currently, induction chemotherapy is one of the standard treatment modalities for patients with locally advanced HNSCC to improve survival and for organ preservation. [3][4][5][6] In a Meta-Analysis of Chemotherapy in Head and Neck Cancer, the addition of induction chemotherapy using cisplatin and 5-fluorouracil to local treatment was associated with an improvement in overall survival (OS) and distant failures. 4 Recently, randomized trials 5,7 revealed induction chemotherapy regimens with docetaxel, cisplatin, and fluorouracil (TPF) significantly improved progression-free survival (PFS) and OS, compared to the conventional regimen of cisplatin and 5-fluorouracil.…”
Section: Introductionmentioning
confidence: 99%